Sikap Ibu Hamil Terhadap Inisiasi Menyusu Dini - Astuti, Siti Choirul Dwi (Journal Midwifery Jurusan Kebidanan Politeknik Kesehatan Gorontalo, 2020)
Early initiation of breastfeeding is still difficult to implement because the mother's knowledge about early initiation of breastfeeding is still lacking. Whereas one of the factors that determine the mother's attitude towards early initiation of breastfeeding is because the mother has information about early initiation of breastfeeding. For this reasEarly initiation of breastfeeding is still difficult to implement because the mother's knowledge about early initiation of breastfeeding is still lacking. Whereas one of the factors that determine the mother's attitude towards early initiation of breastfeeding is because the mother has information about early initiation of breastfeeding. For this reason, the purpose of this study is the influence of knowledge on the mother's attitude to initiate early breastfeeding. The population in this study were all pregnant women in the third trimester who visited the RB. The study site and 46 samples used were determined using simple random sampling with a study duration of 3 months. This research includes analytical research with a cross-sectional approach. The method used to analyze the data using Chi Square. The questionnaire used as a measuring tool that has been tested for validity and reliability. The results of this study of respondents who have the characteristics of a healthy reproductive age, highly educated and well-informed will have a positive attitude towards early initiation of breastfeeding. The conclusion of this study is that there is a relationship between age, education and knowledge of mothers' attitudes in early initiation of breastfeeding. on, the purpose of this study is the influence of knowledge on the mother's attitude to initiate early breastfeeding. The population in this study were all third-trimester pregnant women who visited the RB where the study was conducted and the sample was determined using simple random sampling. This research includes analytical research with a cross-sectional approach. The method used for data analysis using Chi-Square. The questionnaire is used as a tool that has been tested for validity and reliability. The results of this study, the majority of respondents have the characteristics of healthy reproductive age, secondary education and good knowledge have a positive attitude towards early initiation of breastfeeding. This study concludes that there is a relationship between age, education, and knowledge of mothers' attitudes in the early initiation of breastfeeding.